Simulation and Planning of a 3D Spray Painting Robotic System - João Marcelo Casanova Almeida Tomé Santos (2021)
In this dissertation a 3D spray painting robotic system is proposed. This system has realistic spray simulation with sufficient accuracy to mimic real spray painting. It also includes an optimized algorithm for path generation that is capable of painting non trivial 3D designs. The simulation has 3D CAD or 3D scanned input pieces and produces a realistic visual effect that allows qualitative analyses of the painted product. It is also presented an evaluation metric that scores the painting trajectory based on thickness, uniformity, time and waste of paint.